Effects of antioxidant supplementation for polycystic ovary syndrome - Łopacińska, Olga; Stańczyk, Katarzyna; Korn, Aleksandra; Czarnecka, Karolina; Wójcik, Emilia; Korczak, Anna; Jędrzejczyk, Justyna; Szewczyk, Oliwia; Olek, Ewa; Burda, Katarzyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Polycystic ovary syndrome is the most common endocrinopathy in women, with a prevalence ranging from 10% to 13%. Oxidative stress and decreased antioxidant levels contribute to the development of various diseases, and one of them is polycystic ovary syndrome. The aim of this review is to provide an overview of the current knowledge about the effects of antioxidant administration in PCOS treatment. A brief description of the state of knowledge: Oxidative stress is an imbalance between increased levels of reactive oxygen species and a decreased efficiency of antioxidant mechanisms, which can potentially cause damage. The harmful effects of free radicals might be neutralized by antioxidants obtained from the diet, such as polyphenols, vitamins C, and E. These compounds improve several aspects of the PCOS pathomechanism, including hormonal imbalance, glucose metabolism, lipid profile, and ovarian functionality. Conclusions: The outcomes of all the reviewed studies in this paper indicate that antioxidants such as resveratrol, curcumin, vitamin C and E, N-acetylcysteine, and melatonin have therapeutic potential in the management of PCOS. However, currently antioxidant therapies cannot be recommended in PCOS therapy since there is a need for more prospective randomized clinical trials on a larger sample to establish a long-term effects of antioxidants supplementation in PCOS, the optimal dosage, and finally to assess which antioxidant is the most efficient in PCOS treatment.